(untitled) (Ameghiniana, 2013)
Palynological studies in the sandstones and shales of the Itararé Sub-group in the White’s Section, from Lauro Müller, Santa Catarina, Brazil, yields a large variety of miospores in the assemblage, with Triletes, Monosaccites, Disaccites, Striatiti, Plicates and lncertae sedis forms. The assemblage comprises 53 species, with one new, Neoraistrickia baculicapillosa, sp. nov. Trilete forms constitute 70% of the palynological content, mainly the genera Punctatisporites, Granulatisporites, Deltoidospora and Calamospora. Pollenites and Incertae sedis are the other componentes of the assemblage. Among the Pollenites group, monosaccate forms dominate in the palynological assemblage. The genera Cordaitina, Potonieisporites and Virkkipollenites are well represented. Striatiti (Protohaploxypinus, Striatopodocarpites, Lueckisporites and Vittatina) are represented, but in low frequence in the assemblage. Palynological content analysis suggests a Lower Permian age, probably Sakmarian for Itararé Sub-group, in the studied area, according correlations with others miospores assemblages from Gondwana.